El quechua de Sihuas: una isla lingüística - Quesada Castillo, Félix (2013)
In this study we characterize the structure of the Quechua spoken in the different communities in the province of Sihuas, area that lies near the northeast border of Departament of Ancash, focusing on the phonological and morphological levels. The importance of this variety lies in the fact that it preserves the consonant system and certain morphological characteristics of Proto-Quechua. By examing this variety, we have discovered the preservation of the retroflex / ĉ /, converted into / č / in other varieties; the retention of the suffix / -ku / not only for the interrogative but also for the negative form; apart from other features what we will approach in the corresponding sections. These phonological and morphological traits existing only in this variety characterize this dialect as an dialectal island surrounded by other varieties that lack this particular feature. These characteristics will contribute with the reconstruction of Proto-Quechua solidly based on empirical foundations. Also, we propose the geographical areas constitute its origin and the expansion router until this present location.